Did the National Lockdown in Saudi Arabia Reduce Lower Respiratory Illnesses in Children? - Alharbi, Nasser S.; Alnasser, Yossef; Alenizi, Ahmed S.; Alanazi, Alnashmi S.; Alharbi, Abeer H.; AlQurashi, Faisal O.; Nafisah, Ibrahim; Yousef, Abdullah A. (Frontiers in Pediatrics, 2021)
Objectives: This study aims to explore the effect of lockdown and early precautionary measures implemented in Saudi Arabia on number of pediatric hospitalizations due to lower respiratory illnesses (bronchiolitis, asthma, and pneumonia). Methods: This is a retrospective cross-sectional study aims to review patients from four major hospitals in Saudi Arabia. All pediatric hospitalizations secondary to asthma, bronchiolitis, and pneumonia during the months of the lockdown (March, April, and May) in 2020 were documented. Then, they were compared to the previous 2 years. Variables like number of hospitalizations, oxygen requirement, mechanical ventilation, admission to the intensive care unit (ICU), length of stay, and results of viral studies were collected. Results: We included 1,003 children from four different centers. Males were slightly higher than females (55.8% vs. 44.2%). Total number of hospitalizations in 2020 was 201, significantly lower than 399 and 403 hospitalizations in 2019 and 2018, respectively (P < 0.01). The major drop happened on the months of April and May. Although bronchiolitis hospitalizations' dropped by more than half in 2020 compared to the previous 2 years, it was not statistically significant (P = 0.07). But, asthma hospitalizations were significantly less in 2020 compared to the previous 2 years (49–65% reduction, P = 0.003). Number of pneumonia cases were lowered in 2020 compared to the previous 2 years. However, proportion of pneumonia diagnosis to total hospitalizations increased in 2020 (55% compared to 50% and 35%). There was a surge of viral testing during a period of uncertainty in the early phase of the pandemic. This total reduction in hospitalization was not associated with higher oxygen requirements, mechanical ventilation, ICU admissions or longer hospital stay. Conclusions: Lockdown and precautionary measures executed during the early phase of COVID-19 pandemic helped decrease the number of hospitalizations due to lower respiratory illnesses in Saudi Arabia. Reduction in hospitalizations seems less likely to be secondary to hospital avoidance or delayed presentations as number of ICU admission and oxygen requirements did not increase. The post pandemic pattern of respiratory illnesses among children needs further research.